(untitled) (World Economics and Finance Bulletin, 2024)
The research focuses on Analysis and measurement of the impact of public debt on public spending, as public debt is one of the sources of financing the deficit in the general budget, which in turn reflects on the structure of economic activity in Iraq, and the research problem revolves around what Iraq suffers from excessive public spending, especially consumer spending in light of unsecured public revenues, especially the main resource on which the general budget depends, namely oil, which is subject to conditions beyond control production, pricing and marketing, forcing the state to resort to public debt to cover the budget deficit, and on this basically, continuing to borrow leads to an increase in the volume of The public debt is reaching levels that exceed the state’s ability to meet its financial obligations to creditors, which negatively affects the economic activity of the state and the occurrence of paralysis in development efforts and the accompanying economic and social repercussions, in addition, the increasing amount of funds resulting from the burden of servicing public debt that can be used to finance economic development plans, and: The existence of a common integration between public debt and public spending in both current and investment, and that 13.3% of the imbalance in the previous period is corrected in the subsequent period after any shock to the independent variables and affects the dependent variable, while the most important recommendations indicate the need to adopt a fiscal policy consistent with monetary policy, aimed at rationalizing public spending to reduce pressure on the state budget, which in turn reduces the need for internal or external borrowing.